The Effect of Interactive Notifications and Gamification on User Engagement in Learning Mobile Applications - Salsabila Dwi Fitri; Yorasakhi Ananta (SYSTEMIC RESEARCH: Systemic and Information Technology Journal, 2025)
Mobile learning applications are increasingly developing as interactive and flexible educational tools. One important factor in increasing user engagement is the use of interactive notifications and gamification elements. Personal, real-time, and adaptive notifications can increase user response to digital learning. On the other hand, the application of gamification such as points, badges, leaderboards, and challenges has been proven to strengthen user motivation and learning experience. This article aims to systematically examine the effect of interactive notifications and gamification on user engagement in mobile learning applications based on literature studies. This study analyzes a number of scientific articles from indexed international journals over the past 10 years. The results of the review show that the combination of contextually adjusted notification features and intrinsic motivation-based gamification strategies contribute positively to user retention and increased active engagement in the digital learning process. These findings support the importance of designing learning information systems that prioritize user experiences based on motivation and real-time responses.